Study of the interaction between N-confused porphyrin and bovine serum albumin by fluorescence spectroscopy - Yu, Xianyong; Liu, Ronghua; Yi, Rongqiong; Yang, Fengxian; Huang, Haowen; Chen, Jian; Ji, Danhong; Yang, Ying; Li, Xiaofang; Yi, Pinggui (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2011)
The interaction between N-confused porphyrins (NCP) and bovine serum albumin (BSA) was studied by fluorescence and UV–vis spectroscopy. The quenching mechanism, binding constants, thermodynamic parameters, and binding distance were obtained. [Display omitted] ► We explored the interaction of BSA and NCP by spectroscopic methods. ► The quenching mechanism is static quenching or static and dynamic quenching. ► Hydrophobic interaction plays a major role in the binding process. ► The binding constants, binding sites and thermodynamic parameters were calculated. ► The substitution in benzene ring affects the interaction. The fluorescence and ultraviolet spectroscopy were explored to study the interaction between N-confused porphyrins (NCP) and bovine serum albumin (BSA) under imitated physiological condition. The experimental results indicated that the fluorescence quenching mechanism between BSA and NCP was static quenching procedure at low NCP concentration at 293 and 305 K or a combined quenching (static and dynamic) procedure at higher NCP concentration at 305 K. The binding constants, binding sites and the corresponding thermodynamic parameters Δ H, Δ S, and Δ G were calculated at different temperatures. The comparison of binding potency of the three NCP to BSA showed that the substituting groups in benzene ring could enhance the binding affinity. From the thermodynamic parameters, we concluded that the action force was mainly hydrophobic interaction. The binding distances between NCP and BSA were calculated using Förster non-radiation energy transfer theory. In addition, the effect of NCP on the conformation of BSA was analyzed using synchronous fluorescence spectroscopy.